1971
DOI: 10.2337/diab.20.3.140
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Protease with Specificity for Insulin from Rat Muscle

Abstract: A soluble enzyme partially purified from rat muscle is described which degrades insulin proteolylically with a high degree of specificity. The enzyme attacked proinsulin and proinsulin intermediates at only 3 per cent and 10 per cent of the rate with insulin, respectively. Proinsulin competitively inhibited insulin degradation with an inhibition constant of 0.28 JJM, whereas the K m for insulin was 0.18 /J.M. Insulin derivatives with amino or carboxyl terminal residues removed were attacked with K m 's about f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

1972
1972
2001
2001

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(36 citation statements)
references
References 4 publications
1
34
0
1
Order By: Relevance
“…Insulin-degrading activity was demonstrated in the soluble fraction of cells from rat diaphragms (10). Brush partially purified the rat skeletalmuscle enzyme and demonstrated that this sulfhydryl enzyme proteolytically degraded insulin, but not proinsulin (11). A similar enzyme has been demonstrated in other rat tissues (12,13), and a similar enzyme in the liver has been partially purified (7).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Insulin-degrading activity was demonstrated in the soluble fraction of cells from rat diaphragms (10). Brush partially purified the rat skeletalmuscle enzyme and demonstrated that this sulfhydryl enzyme proteolytically degraded insulin, but not proinsulin (11). A similar enzyme has been demonstrated in other rat tissues (12,13), and a similar enzyme in the liver has been partially purified (7).…”
mentioning
confidence: 73%
“…After centrifugation, the supernatant and precipitate were counted in a Packard autogamma spectrometer. One unit of enzyme activity is that amount of enzyme that converts 1 fmol of insulin to acid-soluble material per min (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IDEA, purified to homogeneity, has been characterized recently as a sulphydryl-dependent protease, which specifically degrades insulin at physiological hormone concentrations into peptides smaller than the A-chain of insulin and can be inhibited by several protease inhibitors [14,15]. Though red blood cells are not a known target tissue of insulin action, they do carry insulin receptors, and erythrocyte IDEA appears to show properties similar to the insulin degrading proteases of insulinsensitive tissues from animal sources [1][2][3][4][5]10] and especially similar to the enzyme purified from human skeletal muscle [20].…”
Section: Discussionmentioning
confidence: 99%
“…A cytosolic soluble enzyme which rapidly degrades insulin by proteolysis has been found in many animal [1][2][3][4][5][6][7][8][9][10][11][12] and some human tissues [12][13][14][15][16][17][18][19][20]; reductive disulphide cleavage of insulin, i. e. a glutathione-insulin-transhydrogenase activity, has also been described [11,[20][21][22]. Evidence has accumulated that both insulin action and degradation might be mediated through binding of insulin to specific receptors on the plasma cell membrane as the initial step [12,13,18,19,23,24], although the precise nature of this relationship remains to be elucidated.…”
mentioning
confidence: 99%